Answer
y = 1(x +1) - 3
Explanation
A quadratic equation of the form y = ax^2 + bx + c
This written in complete the square form provides you with the vertex (either a maximum or minimum point depending on the equation).
This results in y = a(x + p) + q
Where - p is the x value and q is the y value of turning point.
For graph 22, x = -1 and y = -3
Therefore, the equation is of the form
y = a(x + 1) - 3 (*)
We still need the value a, this can be obtained by using the y-intercept we are given.
We are told x = 0 when y = -2
Substitute this in (*) equation:
-2 = a(0+1) - 3
-2 = a - 3
a = 1
Therefore final equation is
y = 1(x +1) - 3
This should provide you with the train of thought of how the second question should also be tackled.
If unsure about why the equation
y = a(x + p) + q gives the vertex ask in comments I will respond
5040, I looked up the factorial of 7
Answer:
49
Step-by-step explanation:
No she is not correct because we dont have only one angle angle G is 90.
So we can easily find the angle D
180-(90+41) =49
Answer:
b.
( -3, -5)
Step-by-step explanation:
6x + 13 = 2x + 1
6x -2x = 1-13
4x = -12
x = -12/4 = -3
y = 6x + 13
y = 6(-3) +13 = -18+13 = -5
(x, y) = (-3,-5)
The GCF here is 2
2(z - 11z + 24)
i assume your question is wrong.. or you printed it inaccurately
because the 1st term should indicate the highest exponent however the 1st and 2nd terms are having the same exponent!!